Evaluation of host-specificity of Zygogramma bicolorata Pallister (Coleoptra: Chrysomelidae) for the biological control of Parthenium hysterophorus L. (Asteraceae: Heliantheae) in Nepal - Bajracharya, Ajaya Shree Ratna; Thapa, Resham Bahadur; KC, Gopal Bahadur; Pradhan, Shree Baba; Ranjit, Jagat Devi (Journal of Agriculture and Natural Resources, 2021)
Host-specificity test of Zygogramma bicolorata Pallister (Coleoptra: Chrysomelidae) was conducted in the field and laboratory of National Entomology Research Center, Khumaltar, Lalitpur, Nepal during April to September, 2017. Multiple-choice and no-choice tests were conducted on Agerataum houstoniamum Mill., Bidens pilosa L., Chrysanthemum indicum L., Dahlia pinnata Cav, Guizotia abyssinica L., Helianthus annuus L., Lactuca sativa L., Parthenium hysterophorus L., Perilla frutescence L., Xanthium strumarium L., Zinnia elegans Jacq. and Jasminum officinale L. Among tested plant species, P. hysterophorus was only a preferred host of Z. bicolorata on which both larvae and adults fed. Ovipostion, larval development, pupation and adult emergence of Z. bicolorata occurred successfully on P. hysterophorus completing its life cycle. Larvae consumed H. anuus but could not pupate, and adults fed on it when starved for 5 days in no-choice test. Both adults and larvae of Z. bicolorata consumed X. strumarium and completed larval and pupal developments, but adults did not oviposit. Adult longevity was significantly reduced after feeding on H. annus (19.00 days) and X. strumarium (29.33 days) compared to P. hysterophorus (83.33 days).